Thermal degradation characteristics, kinetics, thermodynamic, and reaction mechanism analysis of pistachio shell pyrolysis for its bioenergy potential - Gupta S.; Gupta G.K.; Mondal M.K. (My University, 2025)
The research work aims to estimate the bioenergy potential of pistachio shell and study its degradation kinetics which is necessary for the efficient design and optimization of thermochemical processes for bioenergy generation. Initial characterizations (proximate, ultimate, higher heating value, and compositional analysis), kinetic study, and thermodynamic analysis accompanied by reaction mechanism are investigated. Physicochemical characterization results confirmed high volatile matter (~ 79.8 wt%) and high heating value (16.85 MJ/kg) of pistachio shell. Thermogravimetric analysis (TGA) is performed at four different heating rates of 10, 20, 30, and 40 °C/min under nitrogen gas flow rate from ambient temperature to 900 °C. TGA results show the three-stage pyrolysis reaction which involves removal of moisture and light volatiles, degradation of cellulose and hemicellulose, and decomposition of lignin. The result also reveals that maximum degradation occurred in the temperature range of 200–400 °C. For calculating the kinetic (activation energy and pre-exponential factor) and thermodynamic parameters (enthalpy, entropy, and Gibbs free energy), different iso-conversional models, i.e. Flynn-wall-Ozawa (FWO), Kissinger–Akahira–Sunose (KAS), Starink, and Friedman, are employed which gives the average value of activation energy as 168.86, 165.80, 166.29, and 190.10 kJ/mol, respectively and the pre-exponential factor values lie in the range of 107-1021 s−1. The average values of Gibbs free energy calculated for FWO, KAS, Starink, and Friedman methods are 182.09, 182.15, 182.13, and 181.42 kJ/mol, respectively. Criado method and Z plot are showing complex reaction mechanism. The results of kinetics and thermodynamic study reveal pistachio shell is an efficient biomass for bioenergy production. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.